Cultural Identity, Moral Wisdom, and Creative Innovation, Insights from Melanau Folklore - Hishamuddin, Siri; Hafizan, Mohamad Naim; Abdul Walid, Ali (2025)
Indigenous oral traditions are not merely remnants of the past, they are living vessels of cultural memory, moral guidance, and collective identity. For the Melanau of Sarawak, Malaysia, folklore has long carried more weight than casual storytelling. It operates as a subtle yet powerful means of passing down ethical principles, ecological wisdom, and shared social codes from one generation to the next. As part of the world’s intangible cultural heritage, Melanau tales reflect a vision of life in which human conduct, spiritual belief, and environmental care are woven tightly together. Yet, under the relentless currents of globalization and the breakneck pace of digital change, these traditions risk slipping into obscurity. UNESCO’s 2003 Convention on the Safeguarding of the Intangible Cultural Heritage makes it clear that such knowledge systems need urgent and intentional preservation. In Southeast Asia’s diverse cultural tapestry, Melanau folklore is distinctive local in flavour yet resonating with universal human concerns: perseverance, responsibility toward the community, and a harmonious relationship with both the visible world and the unseen. Despite this richness, scholarly attention to Melanau folklore remains surprisingly thin. Much of what exists leans toward ethnographic description, leaving less room for structured exploration of the moral underpinnings within these stories. This absence leaves an incomplete picture of how these narratives shape the moral compass of the community. The present study seeks to bridge this gap through a qualitative literary analysis of 24 folk narratives recorded by Harold Stephen Morris in 1997. From this body of work, four recurring moral domains emerge Personal Development and Growth, Social and Cultural Values, Interactions with the Supernatural, and Environmental Stewardship. Together, they form the scaffolding of the Melanau moral world. Ultimately, the objectives are to map out this moral architecture and to imagine how it might be revitalized in modern contexts from educational programs to creative industries to sustainability efforts. By reframing these age-old stories as both heritage and resource, the research hopes to ensure they remain not just remembered but actively lived and reinterpreted for generations to come.